Peer support as a bridge for participation in prison activities and services: A qualitative study with foreign national prisoners - Croux, Flore (Criminology & criminal justice, 2023)
This paper investigates the role of informal peer support as a bridge for participation by foreign national prisoners in prison activities (e.g. education, work, sports activities, library) and services (e.g. psychologist, doctor). A total of 51 individual interviews, following an appreciative inquiry perspective, were conducted with foreign nationals in four prisons in Flanders (Belgium). In terms of leading foreign nationals to prison activities and services, the findings reveal four types of informal peer support: informational support, instrumental support, emotional support, and social companionship. Moreover, during participation in these prison activities and services, three types of informal peer support emerged: informational support, instrumental support, and social companionship. Peer support seems to be a ‘form of survival’ for foreign nationals to overcome barriers experienced in accessing prison activities and services and difficulties during participation in such prison activities and services.